Stokely Carmichael : the story of Black power - Johnson, Jacqueline (Englewood Cliffs, NJ : Silver Burdett, 1990)
A biography of the man who made famous the words "Black Power" as he fought for the rights of black people in this country, and later settled in Africa where he organizes young Africans to work for their rights.
Includes bibliographical references and index.
Keywords: Carmichael, Stokely -- Juvenile literature; African Americans -- Biography -- Juvenile literature; Civil rights workers -- United States -- Biography -- Juvenile literature; Black power -- United States -- Juvenile literature; African Americans -- Civil rights -- Juvenile literature